SUPPLY OF POLITICAL SERVICES AND SUPPORT OF THEM - Valdas Pruskus (Problemos)
Political services to users (electors) are supllied by political organizations and single politicians. In addition to that primary suppliers also suppliers-middlepersons take part in realization of them. They are political agents (functionners of political organizations) and special middlepersons (employees of mass media, advertising and sociological services, politologists whose services are used by political organizations). In the present article their place and role in supply of political services to users are described. Three level (channel) system of supply of political services is analysed: 1) supply of political services through zero-channel, i.e. through direct link between the producer and the user of the political service; 2) there is one middleperson in the realization channel of political service between the producer and the user of the political service; 3) tho-level channel of realization of a political service which involves the participation of two middlepersons. Avantages and imperfections of the above-mentioned channels of realization of political services are discussed. It is concluded that a political organization must to try to select the channel of supply of political services as correctly as possible after the scrupulous evaluation of all its advantages and imperfections. The more the choice of such channel affects also the total market of political services. Also the price of the political service and the opinion of the users (electors) on the offered political product depends on this choise.